2014
DOI: 10.1111/1574-6968.12488
|View full text |Cite
|
Sign up to set email alerts
|

Role of environmental survival in transmission ofCampylobacter jejuni

Abstract: Campylobacter species are the most common cause of bacterial gastroenteritis, with C. jejuni responsible for the majority of these cases. Although it is clear that livestock, and particularly poultry, are the most common source, it is likely that the natural environment (soil and water) plays a key role in transmission, either directly to humans or indirectly via farm animals. It has been shown using multilocus sequence typing that some clonal complexes (such as ST-45) are more frequently isolated from environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
168
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 135 publications
(165 reference statements)
2
168
0
6
Order By: Relevance
“…In Canada, Park and Sanders (1992) reported 88% of C. jejuni and 4% C. coli in vegetables purchased from outdoor markets and supermarkets while in Malaysia, Chai et al, (2007) reported 40.7% C. jejuni and 35.2% C. coli from supermarkets. The high isolation rate of C. jejuni as opposed to C. coli supports the theory that C. jejuni is more resilient to environmental stresses (Gonzalez and Hänninen, 2012;Bronowski et al, 2014); as Chai et al, (2009) also failed to isolate C. coli from soil and manure in Malaysia.…”
Section: Resultssupporting
confidence: 54%
“…In Canada, Park and Sanders (1992) reported 88% of C. jejuni and 4% C. coli in vegetables purchased from outdoor markets and supermarkets while in Malaysia, Chai et al, (2007) reported 40.7% C. jejuni and 35.2% C. coli from supermarkets. The high isolation rate of C. jejuni as opposed to C. coli supports the theory that C. jejuni is more resilient to environmental stresses (Gonzalez and Hänninen, 2012;Bronowski et al, 2014); as Chai et al, (2009) also failed to isolate C. coli from soil and manure in Malaysia.…”
Section: Resultssupporting
confidence: 54%
“…These results suggest that extracellular C. jejuni cells switch to the coccoid form, probably because of the unfavorable aerobic conditions in the extracellular medium. Indeed, C. jejuni is a microaerophilic bacterium and, in the presence of oxygen, it undergoes a short transitional resistance state reflected by morphological changes, including a switch to the coccoid form and a reduction in size, representing the dormant state of C. jejuni (23,43,44). It is possible that the coccoid form of C. jejuni is not picked up by the amoeba, which would explain why no intracellular C. jejuni was detected at 24 h. This possibility needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that Acanthamoeba castellanii promotes the extracellular growth of C. jejuni in cocultures at 37°C under aerobic conditions, even without direct contact between the two microorganisms (21). In addition, it has been suggested that some waterborne protozoa might act as vehicles and reservoirs to increase the survival of Campylobacter in intensively reared poultry (19,22,23). Furthermore, tolerance to low pH and various temperatures and resistance to disinfection by chlorination are higher when C. jejuni is incubated in the presence of waterborne protozoa (attached or internalized), compared with the planktonic state (19,(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Temperature is an important determinant factor for the survival of Campylobacter spp. in water [123], cold temperatures favors for the survival of campylobacters in water, when temperature increases (16 °C and higher), Campylobacter populations in water decline rapidly. This is perhaps due to an increase in metabolic activities and rapid utilization of all nutrients available at the expense of other functions including culturability [117].…”
Section: Survival Strategies/mechanisms Of Campylobacters In the Envimentioning
confidence: 99%
“…in harsh environments [123], C. jejuni can form biofilm in aquatic environments and on various surfaces in water distribution systems and food processing industries [128]. Aerobic conditions and low concentrations of nutrients can promote biofilm formation by campylobacters so they can survive within polymicrobial biofilm [129][130][131].…”
Section: Survival Strategies/mechanisms Of Campylobacters In the Envimentioning
confidence: 99%